(3c-4)=

Simple and best practice solution for (3c-4)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (3c-4)= equation:


Simplifying
(3c + -4) = 0

Reorder the terms:
(-4 + 3c) = 0

Remove parenthesis around (-4 + 3c)
-4 + 3c = 0

Solving
-4 + 3c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 3c = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 3c = 0 + 4
3c = 0 + 4

Combine like terms: 0 + 4 = 4
3c = 4

Divide each side by '3'.
c = 1.333333333

Simplifying
c = 1.333333333

See similar equations:

| 3x+7=-32 | | 3x^2-2x-21= | | (7y-2)/3=-4/(y-3) | | 10/2p-6/20=15/20p+9/20 | | Ax-1=bx | | 18-4200/x^2 | | (3x^2+2x-9)-(6x^2-8)= | | 25200/24 | | 7-2800/x^2=0 | | 8/32= | | log(9)7+log(9)4= | | 5x-9=x+6 | | x^2+7x-6=9x-6 | | (3x^7-3x^4+8x)+(6x^7-5x^4+7x)= | | 10=5/2v | | 5=8/x+2 | | x^2-2x-7=1 | | X+20x-8=0 | | 2w/7=6 | | X/3-1=x/4 | | 3/2y=30 | | 12/5=4z | | 3(x-2)-1=-2(4-6x)+3 | | 0=2x^2+5x | | 2a-18.2=a+2.8 | | -x-1=-5 | | 10u+6=3u+48 | | y^2+x^2=r^2 | | x^3+2x^2-29x+42=0 | | oz=tbsp | | 1/4+1/2*2/5 | | 4m+6=m+3 |

Equations solver categories